2019
DOI: 10.1002/anie.201814377
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Noncoding RNA by Microscale Thermophoresis

Abstract: Accurate quantification of the copy numbers of noncoding RNA has recently emerged as an urgent problem, with impact on fields such as RNA modification research, tissue differentiation, and others. Herein, we present a hybridization‐based approach that uses microscale thermophoresis (MST) as a very fast and highly precise readout to quantify, for example, single tRNA species with a turnaround time of about one hour. We developed MST to quantify the effect of tRNA toxins and of heat stress and RNA modification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Hence, the actual copy number of individual tRNAs or specific tsRNAs in any cell type under specific growth or stress conditions remains largely unknown. Microscale thermophoresis has been recently used to measure copy numbers of endogenous tRNAs [54]. As for tsRNAs, copy number estimates for particular tsRNA species have been attempted based on textbook calculations (for instance, in supplementary data in [20]), but these estimates remain experimentally unproven.…”
Section: Identification Of Proteins Associating With Endogenous 5ʹ Tsmentioning
confidence: 99%
“…Hence, the actual copy number of individual tRNAs or specific tsRNAs in any cell type under specific growth or stress conditions remains largely unknown. Microscale thermophoresis has been recently used to measure copy numbers of endogenous tRNAs [54]. As for tsRNAs, copy number estimates for particular tsRNA species have been attempted based on textbook calculations (for instance, in supplementary data in [20]), but these estimates remain experimentally unproven.…”
Section: Identification Of Proteins Associating With Endogenous 5ʹ Tsmentioning
confidence: 99%
“…"Jackpot" tRNAs with extremely and presumably artefactually high read abundance have been reported in prior tRNA-seq results (Pang et al 2014;Jacob et al 2019), and the original YAMAT-seq paper reported a single tRNA-LysCTT gene having approximately 10-fold higher expression than the next most highly expressed gene (Shigematsu et al, 2017).…”
Section: The Promise and Pitfalls Of Quantifying Trna Expression Usinmentioning
confidence: 89%
“…In cases where modifications outside the ASL are lost, tRNA destabilization may account for the negative phenotype ( 74 ). However, when distinct ASL modifications are lost, tRNA remains stable but functionally impaired ( 2 , 15 , 77 ). This is well characterized for combined loss of mcm 5 U34 and s 2 U34, resulting in translational slowdown of the ribosome at CAA and AAA codons read by tRNA Gln UUG and tRNA Lys UUU , respectively.…”
Section: Discussionmentioning
confidence: 99%